“To Preserve This Remnant:” William Apess, the Mashpee Indians, and the Politics of Nullification - Neil Meyer (European Journal of American Studies)
This article situates the work of American Indian writer and activist William Apess in the context of contemporaneous debates around removal of the Cherokee nation from the state of Georgia and the secession crisis brought on by South Carolina. These two national political battles inform the work Apess does with the Mashpee Indian community of Cape Cod, represented by their collected work The Indian Nullification of the Unconstitutional Laws of Massachusetts, Relative to the Marshpee Tribe: or, The Pretended Riot Explained (1835). Building on the scholarship by Maureen Konkle, Andy Doolen, and others, this article argues that Apess frames the state-level political battle of the Mashpee in the larger national context of removal and southern secession as a means of disrupting the political logic of the state of Massachusetts. In seeing the political treatment of the Cherokee by the federal government, Apess rhetorically recasts the Mashpee community as “nullifying” state law as a means to both barter for enhanced rights for the community and, more importantly, call into question what Indian citizenship and sovereignty meant for the most vulnerable forms of Indian community in antebellum New England.